Analysis of Saudi Arabian Television Advertising on Social Changes Post MBS Cultural Reform - Athallah, Reihan Hafidh; Priyoyudanto, Febri (International Journal of Science and Society, 2024)
This study aims to determine the social changes that occur among Saudi Arabian teenagers in the Takki film series; the form of social change that occurs in this film series, how the characters respond to these changes, and how they adapt to the changes that occur. The method used is a descriptive qualitative method, the researcher presents a description or narrative about this film series and is accompanied by articles related to the research object. From the research conducted, it was concluded that there were three important points discussed by researcher regarding the social changes that occurred among Saudi Arabian teenagers, namely gender equality, the limitations of women, and also opportunities for the cinema industry in Saudi Arabia. There is still an imbalance in terms of gender equality, the limitations of women which are very visible in this film series, and how the film industry is still very behind.